Role of N-Cadherin in Epithelial-to-Mesenchymal Transition and Chemosensitivity of Colon Carcinoma Cells - Skarkova, Veronika; Vitovcova, Barbora; Matouskova, Petra; Manethova, Monika; Kazimirova, Petra; Skarka, Adam; Brynychova, Veronika; Soucek, Pavel; Vosmikova, Hana; Rudolf, Emil (Cancers, 2022)
(1) Background: N-cadherin expression, epithelial-to-mesenchymal transition (EMT) and aggressive biological phenotype of tumor cells are linked although the underlying mechanisms are not entirely clear. (2) Methods: In this study, we used two different in vitro cell models with varying N-cadherin expression (stabilized lines and primocultures) and investigated their select biological features including the degree of their chemoresistance both in vitro as well as in vivo. (3) Results: We report that although enforced N-cadherin expression changes select morphological and behavioral characteristics of exposed cells, it fails to successfully reprogram cells to the aggressive, chemoresistant phenotype both in vitro as well as in vivo as verified by implantation of those cells into athymic mice. Conversely, primocultures of patient-colonic cells with naturally high levels of N-cadherin expression show fully aggressive and chemoresistant phenotype pertinent to EMT (in vitro and in vivo), with a potential to develop new mutations and in the presence of dysregulated regulatory pathways as represented by investigated miRNA profiles. (4) Conclusions: The presented results bring new facts concerning the functional axis of N-cadherin expression and related biological features of colon cancer cells and highlight colon cancer primocultures as a useful model for such studies.